2022
DOI: 10.1038/s41598-022-12711-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oat seed transcriptome with regards to proteins involved in celiac disease

Abstract: Oat (Avena sativa L.) is considered to be a healthy food. In contrast to other grain crops, oat is high in protein, lipids, dietary fiber, antioxidants, and uniquely in avenanthramides. The question of whether it can also be consumed by people suffering from celiac disease is still unresolved. The main aim of this study was to extract and sequence genes for potentially harmful avenins, globulins, and α-amylase/trypsin inhibitors in six oat varieties and to establish their variability using PacBio sequencing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…In the study of Leišová-Svobodová et al (2022) , genes for potentially harmful avenins, globulins and α-amylase/trypsin inhibitors were investigated using PacBio sequencing technology of enriched libraries. The research group concluded, that whether oats are less toxic to people with celiac disease is a question of dose.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Leišová-Svobodová et al (2022) , genes for potentially harmful avenins, globulins and α-amylase/trypsin inhibitors were investigated using PacBio sequencing technology of enriched libraries. The research group concluded, that whether oats are less toxic to people with celiac disease is a question of dose.…”
Section: Discussionmentioning
confidence: 99%
“…Storage proteins in oat seeds differ from those in wheat, barley, and rye ( 51 ), and avenins, the oat prolamins, are significantly lower than in wheat and other gluten-containing cereals. Oats contain epitopes with the potential to trigger CD ( 52 ), albeit in low concentrations ( 53 ), as well as immune-reactivity ( 45 ). Some studies found differences in the immunological responses of different oat varieties ( 53 , 54 ).…”
Section: Adverse Reaction To Grain Componentsmentioning
confidence: 99%